2022
DOI: 10.17586/2220-8054-2022-13-6-608-614
|View full text |Cite
|
Sign up to set email alerts
|

Double ring polariton condensates with polariton vortices

Abstract: We study formation of persistent currents of exciton polaritons in annular polariton condensates in a cylindrical micropillar cavity under the spatially localised nonresonant optical pumping. Since polariton condensates are strongly nonequilibrium systems, the trapping potential for polaritons, formed by the pillar edge and the reservoir of optically induced incoherent excitons, is not real in general case. Its imaginary part includes the spatially distributed gain from the pump and losses of polaritons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In narrow ring traps, the radial modes are separated from each other by large distances in energy scale, and, as a rule, condensates occupy single ring modes characterized by the radial quantum number 11 , 13 , 23 (with no nodes in the radial direction). Increasing the width of the annulus of the trap results in exciting higher-order ring states with 21 , 26 , 27 . The role of the radius of the (complex) trapping potential as the control parameter for selective excitation of different vortex states has been emphasized in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In narrow ring traps, the radial modes are separated from each other by large distances in energy scale, and, as a rule, condensates occupy single ring modes characterized by the radial quantum number 11 , 13 , 23 (with no nodes in the radial direction). Increasing the width of the annulus of the trap results in exciting higher-order ring states with 21 , 26 , 27 . The role of the radius of the (complex) trapping potential as the control parameter for selective excitation of different vortex states has been emphasized in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. 26 one has demonstrated that with an increase in the width of the ring (the diameter of the outer wall of the trap), the lower in the radial quantum number n states become lossy, and the condensate has to occupy the higher in n states.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the shift of the pump spot alone is not able to break equivalence between clockwise and counterclockwise directions. In our papers [10][11][12][13][14], we have shown that chirality can be acquired by the polariton system when the shift coexists with another symmetry breaking inclusion, e. g., deformation of the pump beam, defects in the stationary potential landscape. In this case, polariton currents emerge in the condensate manifested as spiral fringes in the images of interference of PL of the condensate and the spherical reference wave.…”
Section: Experimental Observation Of Single Ring Polariton Condensate...mentioning
confidence: 98%
“…In our papers [10][11][12][13][14][15], we have reported observation of polariton condensates in the form of concentric rings. We have shown that by changing the size of the micropillar, on can excite polariton current states in the form of single and concentric rings [10,13,15]. However, in our studies we dealt with polariton condensates in the steady state regime.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation